Culture-Led Transformation of Industrial Cities Towards ‘Creative’ and ‘Smart’ Ones. The Case of Lodz - Sokołowicz, Mariusz; Zasina, Jakub (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The paper aims at identification of the impact of culture on the socio-economic development of the city, by referring to the more and more common trend of transforming urban economies from industrial to ‘creative’ ones. The case study concerns the city of Lodz, where the survey among inhabitants was conducted. Research method was based on a dynamic analysis of the evolution of the city as socio-economic system (evolutionist systemic approach), supported by the questionnaire interview technique. A study revealed that despite many economic struggles, this postindustrial city is able to adapt its cultural offer to today’s needs, emphasizing the territorial specificity and using the creativity of its dwellers as a factor of socio-economic development. The paper presents also selected problems and challenges, to which local cultural policy should respond.